(untitled) (Journal of Ideas in Health, 2021)
Background: This systematic review compares the efficacy and safety of remdesivir between its recipient and non-recipient COVID-19 patients from the recently published randomized controlled trials (RCT). Methods: For eligible trials comparing the above outcomes, a literature search took place in the PubMed database. The reviewed trials data were abstracted and critically appraised using the Cochrane tool. Then, a random-effect meta-analysis followed to compare the risk between the compared interventions in risk ratio (RR). By plying the I2 and Chi2 statistics, the heterogeneity estimation happened. A sensitivity analysis iterated the preliminary meta-analysis using a fixed-effect model. Results: Two eligible RCTs included in this review sourced data from about 833 COVID-19 patients from 115 hospitals in Asia, Europe, and the US. The risk of bias was primarily low. Random-effect meta-analysis suggested a clinical improvement (RR: 1.09; 95% CI: 1.02, 1.16; P=0.02; I2: 0%) and decrease in the risk of any serious side effects (RR: 0.64; 95% CI: 0.43, 0.94; P<0.001; I2: 0%) in the remdesivir treated COVID-19 patients. The rest of the outcomes did not vary between the juxtaposed interventions. Conclusion: Evidence-based on early RCTs suggest that remdesivir is a clinically useful and safe drug to treat COVID-19 patients.